Total Hip and Knee Replacement in Eastern Libya: A Post-Conflict Case Series - Elzwai, Eman; Elhnid, Rasha; Bodalal, Zuhir; Fadli, Mustafa El; Langhi, Salem (International Journal of Statistics in Medical Research, 2014)
Background: Total knee replacement (TKR) and total hip replacement (THR) are effective procedures for alleviating pain and improving hip and knee function. Literature has not covered the experience of developing countries with arthroplasty – especially in an unstable post-conflict setting. Methods: Patient records were obtained from a major surgical center in Benghazi where total joint arthroplasties (TJA) are performed for a period of twenty months and key parameters were analyzed. The patients were followed up on an outpatient basis at regular time intervals (one week, one month, three months and six months) and any complications were documented. Results: A total of 135 total knee (81.5%, n=110) and total hip (18.5%, n=25) replacements were done in Benghazi mostly on elderly (mean age=60.2 years) females (72.2%, n=100). The most common causative pathology in both groups was osteoarthritis (80.6%, n=108). The most common complication was superficial infection (4.4%, n=6) by Staph aureus. The Harris Hip Score and Knee Society Score were used to determine the functional outcomes of THR and TKR respectively – both showing high values. The Short form 36 (SF36) health survey was carried out to assess the patients’ satisfaction levels. For all the axes, the obtained score was over 80%. Discussions: THR and TKR are major orthopedic surgeries that constitute an advancement in the treatment of chronic joint pain. Most of the demographic features of our patients match up well with previous literature – with certain exceptions. There was no difference in thromboembolic incidence between the group of patients who received LMWH and those who simply started early mobilization and physiotherapy. Despite a number of hindrances faced by the hospital due to the conflict (i.e. funding limitations and drug shortages), a low rate of complications was maintained. No thromboembolic incidents or mortalities occurred.